Criminal Law Reform Double Track System (Rehabilitation Versus Prison) On Against The Crime Of Narcotics Abuse In Indonesia - Nelvitia Purba; Mukidi Mukidi; Muhlizar Muhlizar (LEGAL BRIEF, 2022)
Efforts to prevent and eradicate drug abuse are urgent because they can have a systemic effect. Therefore, it is necessary to renew article 127 of Law no. 35 of 2009 (Double Track System) for handling narcotics abuse which so far has emphasized criminal sanctions rather than action sanctions. This research uses normative legal research or can be referred to as doctrinal legal research. The analysis of legal material used is descriptive analysis. The results of the study concluded  (1). The position of criminal  sanctions  and  actions    based  on  article  127  Law Number 35 of 2009   it is clear that there is a regulation, but its application to narcotics abuse has not been effective because it does not take into account the physical and psychological conditions of the perpetrator, which should focus more on rehabilitation than imprisonment (2). The reform of the Criminal Law article 127  Law Number 35 of 2009 (Rehabilitation versus Prison) against narcotics abusers must be carried out immediately because it concerns the future of the nation and also provides aspects of protection and aspects of the public interest.